Mindset, Schism and the Contemporary Transformation of the Anglican Communion - Sandy, Geoffrey A. (Religions, 2025)
The phenomenon of mindset provides a lens to understand more clearly the reasons for, the timing of and the resulting transformation of the Anglican Communion (AC) of its schism. It has been transformed by the interaction between those of a strong conservative mindset and those of a strong progressive mindset. The former are now in schism with those who remain in the AC. The schism is usually explained in terms of opposing doctrinal beliefs and values, which is valid as far as it goes. More fundamental is mindset because it explains why people hold these beliefs and values, which determine how they interact in society. The schism of the AC is chosen as a context or case study to which the scientific research behind mindset is applied. However, it is something that is general and fundamental, which operates in society for both the religious and secular domains.